2021
DOI: 10.1002/mnfr.202001225
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fate and Cardiometabolic Effects of Phenolic Compounds from Red‐Fleshed Apple in Hypercholesterolemic Rats: A Comparative Study with Common White‐Fleshed Apple. The AppleCOR Study

Abstract: The present study aims to investigate the metabolic fate and the cardiometabolic effects of phenolic compounds provided by a red-fleshed apple variety biofortified in anthocyanins (ACN). Wistar rats are fed with high-fat diet (HFD) to induce hypercholesterolemia and supplemented with red-fleshed apple (HFD+R), white-fleshed apple (HFD+W), or an ACN-rich infusion from aronia fruit (HFD+A) providing matched content and profile of ACN. Plasma biochemical parameters, histological analysis, and phenol biological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Metabolic pathways originating from the major (poly)phenols detected in RFA (chlorogenic acid, vanillic acid hexoside, cyanidin-3- O -galactoside, epicatechin and dimer B 2 , quercetin derivatives and phloretin glucoside) were proposed. The (poly)phenolic metabolic profile described in this study was very similar to those observed in other studies in Wistar rats whose diet was supplemented with RFA 77,78 or in a recent intervention study 79 with hypercholesterolemic subjects who consumed 80 g day −1 of freeze-dried RFA.…”
Section: Bioavailability and Metabolism Of (Poly)phenolic Compounds F...supporting
confidence: 86%
“…Metabolic pathways originating from the major (poly)phenols detected in RFA (chlorogenic acid, vanillic acid hexoside, cyanidin-3- O -galactoside, epicatechin and dimer B 2 , quercetin derivatives and phloretin glucoside) were proposed. The (poly)phenolic metabolic profile described in this study was very similar to those observed in other studies in Wistar rats whose diet was supplemented with RFA 77,78 or in a recent intervention study 79 with hypercholesterolemic subjects who consumed 80 g day −1 of freeze-dried RFA.…”
Section: Bioavailability and Metabolism Of (Poly)phenolic Compounds F...supporting
confidence: 86%
“…Moreover, our study, for the first time, provides insights on how apples alter the expression of different CVD related proteins in the rat heart and aorta tissues by a proteome profile analysis. In the frame of this study, our previous work showed cardiometabolic protective effects of both red-fleshed and white-fleshed apples and also aronia infusion supplementation, specifically in the significant reduction of the aorta thickness [ 26 ]. Although no gender differences were observed in this proteomics study, we observed gender differences in some cardiometabolic parameters [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the frame of this study, our previous work showed cardiometabolic protective effects of both red-fleshed and white-fleshed apples and also aronia infusion supplementation, specifically in the significant reduction of the aorta thickness [ 26 ]. Although no gender differences were observed in this proteomics study, we observed gender differences in some cardiometabolic parameters [ 26 ]. Specifically, we observed that the kidney function was improved after all supplementations (both apples and aronia) but only in females (probably related to the higher phenol bioavailability reported in females).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses of fecal microbiota and of gene expression in peripheral blood mononuclear cells (PBMC, which consist of peripheral blood cells having a round nucleus, like lymphocytes and monocytes) have shown minimal differences between the two groups, but genes regulated by red-fleshed apples were immunoglobulin-related, suggesting a potential role in modulating the immune function (Barnett et al, 2021). Finally, both red-and white-fleshed apples seemed to have beneficial effects in hypercholesterolemic rats (Yuste et al, 2021) or in model rats with adenocarcinoma (Bars-Cortina et al, 2020). The benefits of apple and anthocyanin consumption are well established (Knekt et al, 2002;Boyer and Liu, 2004;Cassidy et al, 2015Cassidy et al, , 2016Hyun and Jang, 2016), and apples with high anthocyanin contents could offer effective functional foods, to reduce the incidence of chronic diseases when part of a normal diet.…”
Section: Anthocyanin-rich Applementioning
confidence: 99%